PRODUCTIVITY AND SUSTAINABILITY OF DIFFERENT CROP ESTABLISHMENT METHODS FOR CULTIVATION OF RABI RICE IN WESTERN ORISSA - HALDER, J.; SAHOO, K.C.; KARMAKER, S.K.; NAYAK, R.N. (Annals of Agricultural Research, 2014)
A field experiment was carried out during rabi season of 2004-05 and 2005-06 to study sustainability of different crop establishment methods on growth and yield of transplanted rabi rice. Among the six crop establishment methods raising rice crop by system of rice intensification method (SRI) resulted in significantly higher grain yield (6.09 t/ha) with better expression of yield attributes. Growing rice crop by system of rice intensification method recorded significantly higher number of panicles, panicle weight and filled spikelets panicle/m.